Association between diuretics and successful discontinuation of continuous renal replacement therapy in critically ill patients with acute kidney injury - Jeon, Junseok (Crit Care, 2018)
BACKGROUND: Despite aggressive application of continuous renal replacement therapy (CRRT) in critically ill patients with acute kidney injury (AKI), there is no consensus on diuretic therapy when discontinuation of CRRT is attempted. The effect of diuretics on discontinuation of CRRT in critically ill patients was evaluated. METHODS: This retrospective cohort study enrolled 1176 adult patients who survived for more than 3 days after discontinuing CRRT between 2009 and 2014. Patients were categorized depending on the re-initiation of renal replacement therapy within 3 days after discontinuing CRRT or use of diuretics. Changes in urine output (UO) and renal function after discontinuing CRRT were outcomes. Predictive factors for successful discontinuation of CRRT were also analyzed. RESULTS: The CRRT discontinuation group had a shorter duration of CRRT, more frequent use of diuretics after discontinuing CRRT, and greater UO on the day before CRRT discontinuation [day minus 1 (day − 1)]. The diuretics group had greater increases in UO and serum creatinine elevation after discontinuing CRRT. In the CRRT discontinuation group, continuous infusion of furosemide tended to increase UO more effectively. Multivariable regression analysis identified high day − 1 UO and use of diuretics as significant predictors of successful discontinuation of CRRT. Day − 1 UO of 125 mL/day was the cutoff value for predicting successful discontinuation of CRRT in oliguric patients treated with diuretics following CRRT. CONCLUSIONS: Day − 1 UO and aggressive diuretic therapy were associated with successful CRRT discontinuation. Diuretic therapy may be helpful when attempting CRRT discontinuation in critically ill patients with AKI, by inducing a favorable fluid balance, especially in oliguric patients.